2006
DOI: 10.1051/0004-6361:20054731
|View full text |Cite
|
Sign up to set email alerts
|

CCD astrometric observations of Phoebe in 2003–2004

Abstract: In 2003-2004, we obtained 115 new observations of Phoebe, the 9th Saturnian faint satellite (visual magnitude of about 16.5). We used a large CCD detector (2048 × 2048 pixels) mounted on the 1.56 m astrometric reflector at the Sheshan Station, near Shanghai. In our reduction, an up-to-date catalogue of stars, UCAC2 (Zacharias et al. 2004), was chosen to ensure a proper astrometric calibration. A comparison of our observations to three recently available, high quality ephemerides, including the JPL SAT185 by Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…As a continuation of our program of astrometric observations of natural satellites initiated in 1985, we have undertaken a second campaign of CCD astrometric observations of Phoebe, the first one having been reported by Qiao et al (2006). In this paper, we have presented a very significant number of observations of Phoebe, with 1173 new observed positions of this satellite, representing more than 50 per cent of the data now available on the NSDC data base of the IMCCE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a continuation of our program of astrometric observations of natural satellites initiated in 1985, we have undertaken a second campaign of CCD astrometric observations of Phoebe, the first one having been reported by Qiao et al (2006). In this paper, we have presented a very significant number of observations of Phoebe, with 1173 new observed positions of this satellite, representing more than 50 per cent of the data now available on the NSDC data base of the IMCCE.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, the astronomical community has made considerable efforts to acquire more observations in various ways. Several accurate CCD observations of this satellite were obtained in successive works by Veiga, Vieira Martins & Andrei (2000), Fienga et al (2002), Qiao et al (2006), Peng & Zhang (2006) and Aleshkina, Devyatkin & Gorshanov (2010). As a continuation of our previous observing campaign (Qiao et al 2006), we report here an important number of new observations, namely 1173 observed positions of Phoebe.…”
Section: Introductionmentioning
confidence: 94%
“…This is a quite good result for such a small satellite orbiting rather far from Saturn, and necessarily with reference to absolute positions, when inner satellites with reference to relative intersatellite positions can be expected to be more accurate, as they are less affected by possible systematic errors of star catalogues. However, the improvement in star catalogues, such as UCAC2 used by some recent authors like Qiao et al (2006, 2011), has limited the effect of these possible systematic errors in the recent past. The use of this latest accurate catalogue has also contributed to present here a more reliable updated orbit of Phoebe.…”
Section: Discussionmentioning
confidence: 99%
“…Table 7 shows that the two recent observational sets made by Qiao et al (2006) and Qiao et al (2011) at the Sheshan Station are the most accurate. These two sets, respectively, contain 101 observations made in 2003 and 1173 observations made in the period 2005–08.…”
Section: Analysis and Accuracymentioning
confidence: 99%
“…As the continuation of our systematic programme of astrometric observations of natural satellites initiated in 1985, we successfully developed in the recent years the campaign of observations of Phoebe (Qiao et al 2006). A similar campaign for Triton was carried out and its results are presented here.…”
Section: Introductionmentioning
confidence: 99%